PENERAPAN LINGUISTIK FORENSIK DALAM PENYIDIKAN KASUS PIDANA KEBAHASAAN: STUDI DI POLDA NTB - Almuhajirin Almuhajirin (Universitas Islam Negeri Mataram, 2025)
This research aims to analyze the application of forensic linguistics in the process of investigating criminal language cases carried out by NTB Police Criminal Investigators and linguists. This research uses a descriptive qualitative approach with data collection methods in the form of observation, interviews, and documentation. The data obtained was then analyzed with a forensic linguistic approach to find out the application of linguistics and theoretical approaches used to analyze speech or cases of insult and defamation. The results of this study show that 1. The application of forensic linguistics by investigators of the Directorate of Special Criminal Investigation Unit Sub-Directorate V Cyber in the Investigation. 2. Analysis of Language experts or forensic Linguistics in case of insults and defamation at the NTB regional police.